Advances in Manufacturing Technology Select Proceedings of ICAMT 2018 - Hiremath, Somashekhar S.; Shanmugam, N. Siva.; Bapu, B. R. Ramesh; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume comprises select papers presented at the International Conference on Advances in Manufacturing Technology (ICAMT 2018). It includes contributions from different researchers and practitioners working in the field of advanced manufacturing technology. This book covers diverse topics of contemporary manufacturing technology including material processes, machine tools, cutting tools, robotics and automation, manufacturing systems, optimization technologies, 3D scanning and re-engineering, and 3D printing. Computer applications in design, analysis, and simulation tools for solving manufacturing problems at various levels starting from material designs to complex manufacturing systems are also discussed. This book will be useful for students, researchers, and practitioners working in the field of manufacturing technology. .
Evaluation of Tensile Properties of Nano Clay Filled Madar Fiber Reinforced Polyester Hybrid Composites -- Characterization of Economical Aluminium Mmc Reinforced With Weld Slag Particles -- Optimization of Weld-Bead Parameters Of Plasma Arc Welding Using Ga and Iwo -- Experimental Studies on the Effect of Basalt Powder Inclusion On Mechanical Properties of Hybrid Epoxy And Polyester Composites Reinforced With Glass Fiber -- An Experimental Investigation on Tensile Properties of Hybrid Bio Polyurethane Composite: Modelling and Optimization -- Improvement of Machining Characteristics by Edm with Graphite Powder Mixed Dielectric Medium -- Measuring Industrial Symbiosis Index Using Multi Grade Fuzzy Approach -- Fabrication and Machining Characteristics of Al7075-Red Mud and Al7075-Tic Metal Matrix Composites -- Multi Criteria Optimization of Machining Parameters in Wedm of Titanium Alloy 6242 -- Water Absorption & Density Tests on the Water Hyacinth Based Partial Green Composite -- ExperimentalAnalysis on the Mechanical Properties of Dissimilar Material Joint During Pctig Welding -- Influence of Flux Coating During Dissimilar Welding of Copper With Brass Using Atig Welding Process -- Innovative Nitride Film Deposition on Copper Interconnects of Mems Devices Using Plasma Enhanced Chemical Vapour Deposition Techniques.-Sleep Detection and Alert System for Automobiles -- Numerical Analysis and Design Optimization of Lip Seal Opening Pressure for Automotive Valves -- Mechanical and Microstructural Properties of Multi Axially Forged Lm6 Aluminium Alloy -- Implementation of Lean Concepts Using Value Stream Mapping In Automotive Firm -- Fabrication of Automated Scrap Collector Cum Scrubber For Production Industries -- Enhancement of Mechanical Properties Through Spheroidization Annealing For Low Carbon Steel -- Effect of Rolling Reduction on Microstructure and Mechanical Properties Cu-3%Ti Alloy.-An Investigative Approach to Study The Corrosion Response Of Copper-Brass Tig Welded Samples Using Nitric Acid As The Corroding Agent -- A Review On Mechanical Properties, Tribological, Corrosion and Weldability Studies of Aluminum Composites Processed Using Stir Casting & Ecap Methods -- Characterization and Comparison of Functionally Graded Al/Mg and Al/Al 7075 Metal Matrix Composites Manufactured By Die Casting -- Statistical Quality Control of Torque Wrenches Used In Automotive Assembly Department -- Optimal Sequence Identification in Parallel Flow Line Environment Using Heuristics -- Design and Analysis of Stringer on the Chassis Frame in Load Carrying Vehicle -- Design and Analysis of Active Controlled Prosthetic Hand -- Bio-Degradable Composites from Leaf Wastes for Packing Applications -- A Comparative Study of Flow Characteristics of Bmw-M6 and Audi-R8 Commercial Sports Car Using Flow Design Software -- Mechanical Characterization of Glass Fiber Strengthened Balsa-Depron Composite -- Milling Cutter Flank Wear Prediction Using Ensemble of Pso Optimized Svm and Glm Regression Models -- Investigation on the Corrosion Resistance Characteristics of Automobile Lug Nuts -- Application of Taguchi Method in Optimization of Process Parameters of Electrochemical Machining Of Tic Reinforced Aa6063 Composites -- Performance Analysis of Ss304 Steel Hat-Stringer on the Chassis Frame.-Finite Element Modeling Of Single Spark Material Removal and Heat Flux Distribution in Micro Electro Discharge Machining Process -- Electrochemical Micromachining of Aluminium Alloy Composite -- Analysis on Mechanical Behavior of Binary and Hybrid Al 2014 Metal Matrix Composites -- Study of Forces, Surface Finish and Tool Life on Machining Of Inconel 718.-Investigations on Corrosion Behaviour of Aa 8011 -Zrb2 In-Situ Metal Matrix Composites -- Introducing Various Image Processing Techniques to Improve Topology Optimization Process to Develop Compliant Mechanism Based Micro Gripper -- Study on Tensile Strength of Glass Fiber Reinforced Nanocomposites by Vartm -- Investigations on Wire Spark Erosion Machining Of Aluminium Based Metal Matrix Composites -- Optimization of Coefficient Of Friction for Direct Metal Laser Sintered Inconel 718 -- Experimental and Numerical Investigation on Incremental Forming of Is513cr3 -- Modelling Of Support Vector Mechanism For Green Manufacturability Quantification of Production -- Experimental Study on Surface Roughness and Optimization of Process Parameters Using Ann-Ga in Milling of Super Duplex Stainless Steel Under Dry and Wet Conditions -- Experimental Study On Tool Wear And Optimization of Process Parameters Using Ann-Ga In Turning Of Super Duplex Stainless Steel Under Dry And Wet Conditions -- Multi Response Optimization Using Grey Relation Analysis in Mechanical Micro Drilling (Mmd) Of Titanium - Grade 2 (Cp-Ti G2) -- A Glance Through History Of Automobile Industry & Current Market Study Of Some Of The Legendry Models In India -- Effect of Twist Angle and Rpm on the Natural Vibration of Composite Beams Made Up Of Hybrid Laminates.-Tribological Behavior of Az91-Al2o3 Composites by Powder Metallurgy -- Annealing and Zno Doping Effects on Hydrophilicity and Mechanical Strength of Pvdfnanocomposite Thin Films -- Optimization of Transient State Temperature Distribution Analysis on Diffusion Bonded Joints Of Ti-6al-4v with Ss304l Stainless Steel Alloy -- Optimization of Tribological Properties of Al6061/9%Gr/Wc Hybrid Metal Matrix Composites Using Fgra -- Experimental Study on Mechanical Properties of Super Elastic Alloy -- Framework Execution and Schematic of Jounce Bumper in Two Wheeler Fork -- Finite Element Analysis of Bending and Dynamic Response of a Power Transmission Spur Gear -- Design and Analysis of Composite Parabolic Leaf Spring Under Fatigue Load Condition -- Optimizing Headlamp Focusing Through Intelligent System as Safety Assistance in Automobiles -- Modeling and Validation of Ride Characteristics of All Terrain Vehicle (Atv) -- Effect of Tool Rotation Speed on Joint Characteristics of Under Water Friction Stir Welded Aa2519-T87 Aluminium Alloy -- Investigation of Hardness and Tribological Behaviour of Aluminum Alloy Lm30 Reinforced With Silicon Carbide, Boron Carbide and Graphite -- Friction and Wear Properties of Bio Based Abrasive in A High Friction Composite Material -- Parametric Optimization of Single Cylinder 4 - Stroke Spark Ignition Engine Crankshaft Using Three Different Materials-Aisi 1040, Aisi 4340, Aisi 4140 and Aisi 4615 -- Evaluation and Optimization of Surface Roughness and Metal Removal Rate Through Rsm, Gra, Topsis Techniques In Turning Ptfe Polymers -- Effect of Sintering Temperature on the Microstructure and Forming Behavior of Aa8079 (Al-Cu-Fe-Si-Zn) -- Studies of Welding Process Parameters on Clad Bead Shapes and Its Shape Interactions of Ernicrmo - 10 Claddings Deposited by Gmaw -- Review On Corrosion Behavior of Copper-Brass Weldment Samples During Welding With The Different Corrosive Environment -- Effect on Mechanical Properties of Aluminum Compositesby Inclusion of Silicon Carbide. .
Keywords: Manufactures; Machinery; Coatings; Tribology; Corrosion and anti-corrosives.; Control engineering; Robotics; Automation; Machines, Tools, Processes; Machinery and Machine Elements; Coatings; Tribology; Corrosion; Control, Robotics, Automation